Factors enhancing the adoption of on-demand services digital platforms in South African metros - Nyhuswa, Mbuyiswa (University of the Witwatersrand, Johannesburg, 2023)
The purpose of this study is to examine the factors that enhance the adoption of on-demand services platforms in South African metros and understand if service consumption location impacts a user’s intention to adopt the digital platform. This study uses a quantitative research methodology, using an online survey. Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) theoretical framework was used to construct the online survey instrument and using snowball sampling, 386 valid responses were collected across 8 major South African metros. Descriptive analysis was performed, and the Structural Equation model was conducted to analyse data from the survey questionnaire and evaluate multivariate casual relationships. The study uses confirmatory factor analysis to verify the measurement quality of latent constructs. The results show that performance expectancy, facilitating conditions, hedonic motivation, price value and consumption location have a positive effect on a user’s behavioural intention to adopt on-demand services digital platforms in South African metros, whereas habit does not. The study was limited to only respondents residing within the 8 major metros in South Africa, which therefore has implications on generalisability. These metros are Buffalo City, City of Cape Town, Ekurhuleni Metropolitan Municipality, City of eThekwini, City of Johannesburg, Mangaung Municipality, and Nelson Mandela Metropolitan Municipality This is the first study which has used UTAUT2 to explain adoption of on-demand services digital platforms in South African metros. Further, the study contributes to the theory by adding a new construct consumption location to test its effect a user’s intention to adopt on-demand services digital platforms. Further theoretical and practical implications are discussed
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business Johannesburg, 2023
Keywords: On-demand service; Digital platform; Adoption; UTAUT2; Consumption location; South Africa; UCTD; SDG-8: Decent work and economic growth